Les grèves d’étudiants au quartier latin au temps de François Villon - Sophie Brouquet (Les Cahiers de Framespa)
A corps united by age, sex, and awareness of its higher intellectual status, the Medieval University demonstrated a strong attachment to its privileges. This spirit was coupled with real independence, dearly acquired against the municipal, ecclesiastical, and royal authorities. The history of the University of Paris is made up of these more or less long, more or less violent conflicts which agitated teachers and students. Their origin was often the same, the defense of privileges that used all the instruments put at the service of the scholars and provided in the university’s founding statutes—strike, cessation of courses, dispersion—but also by much more violent actions of which poet François Villon was the actor and spectator between 1441 and 1445.